Sono-assisted adsorption of a textile dye on milk vetch-derived charcoal supported by silica nanopowder. - Jorfi, Sahand; Darvishi Cheshmeh Soltani, Reza; Ahmadi, Mehdi; Khataee, Alireza; Safari, Mahdi (Journal of Environmental Management, 2017)
This study was performed to assess the efficiency of silica nanopowder (SNP)/milk vetch-derived charcoal (MVDC) nanocomposite coupled with the ultrasonic irradiation named sono-adsorption process for treating water-contained Basic Red 46 (BR46) dye. Field emission scanning electron microscopy (FE-SEM), X-ray diffraction (XRD), Brunauer–Emmett–Teller (BET) and Fourier transform infrared spectroscopy (FT-IR) were performed for the characterization of as-prepared adsorbent. The sono-assisted adsorption process was optimized using response surface optimization on the basis of central composite design by the application of quadratic model. Accordingly, the color removal can be retained more than 93% by an initial BR46 concentration of 8 mg/L, sonication time of 31 min, adsorbent dosage of 1.2 g/L and initial pH of 9. The pseudo-second order kinetic model described the sono-assisted adsorption of BR46 reasonably well (R 2 > 0.99). The intra-particular diffusion kinetic model pointed out that the sono-assisted adsorption of BR46 onto SNP/MVDC nanocomposite was diffusion controlled as well as that ultrasonication enhanced the diffusion rate.